Characteristics Of Partial Mithchondrial Cytochrome Oxidase Sub Unit 1 Gene Of Honey Bee Apis dorsata Binghami [Hymenoptera: Apidae] From Minahasa, North Sulawesi, Indonesia: Characteristics Of Partial Mithchondrial Cytochrome Oxidase Sub Unit 1 Gene Of Honey Bee Apis dorsata Binghami [Hymenoptera: Apidae] From Minahasa, North Sulawesi, Indonesia - Yermia Semuel Mokosuli; Revolson Alexius Mege; Jantje Pelealu; Max Tulung (Universitas Negeri Manado, 2020)
The aims of this study were to characterize the mitochondrial cytochrome oxidase subunit 1 gene (CO1) of Apis dorsata from Minahasa, North Sulawesi. Apis dorsata Binghami used in this study was obtained from the natural colony in Klabat forest, Airmadi forest and Kombi forest. From each native bee colony, ten workers were taken (n = 30). Femur hind legs used for subsequent DNA extraction were amplified by PCR, underwent electrophoresis and then sequenced. CO1 sequences then were matched with BLAST to obtain sequences from the NCBI that have high levels of homology (>90%). The results showed that the universal primer LCO -1490 and HCO - 2198 success amplify the gene CO1 Apis dorsata of Minahasa. Based on the phylogeny tree, Apis dorsata derived from forest Airmadidi and forest Kombi have the same CO1 sequences but have had differences with Apis dorsata from forests Klabat. BLAST analysis results showed that the partial mitochondrial CO1 sequences Apis dorsata of Minahasa has the highest rate of 94 % similarity with similar sequences recorded in the NCBI gene bank.